Efektivitas Rekrutmen Pegawai di SPBU Coco Pertamina Retail Medan - Yusmaniar Kurniawati Sirait; Abdul Kadir; Beby Masitho Batubara (Universitas Medan Area, 2021)
Human resources become the most important part in the survival of a company. Human resources are the most valuable investment and the ultimate foundation of a company's survival. One aspect to the success of the company can be seen from the policy of the leader of a problem in this case how the recruitment system established by the company whether to promote most of the employees from within the organization or lift from the outside to fill the void at all levels. In addition, whether the emphasis is on just filling vacancies or appointments for long-term purposes.The purpose of this study to determine the effectiveness of employee recruitment at gas stations COCO Pertamina Retail Medan.The criterion or indicator of the effectiveness of Tangkilisan, (2005: 141), among others, Target Achievement, Adaptation Capacity (Flexibility), Job Satisfaction, Responsibility. This research is in the form of descriptive qualitative research which the writer do interview technique. Based on Results Of Research That Has Been Spoken, Then Writers Can Draw Conclusions Outline that, Effectiveness Recruitment Staff at Gas Station COCO Pertamina Retail Medan Quite Effective.